The existence of a tour object is affected by the amount of the incoming visitor. Sea World Indonesia as one of the wisata aquatik objects in Indonesia also has to be able to see visitors as a detennining factor and as a main priority. It means without the visitors, the existence of the tour object means nothing. Therefore the best service and the adequate medium in enjoying Sea World Indonesia deserve an attention from the company it self. This research is aimed to identify any kinds of attribu - Darmaningsih .; Popong Nurhayati; Anna Fatchiya (Buletin Ekonomi Perikanan, 2006)
The existence of a tour object is affected by the amount of the incoming visitor. Sea World Indonesia as one of the wisata aquatik objects in Indonesia also has to be able to see visitors as a detennining factor and as a main priority. It means without the visitors, the existence of the tour object means nothing. Therefore the best service and the adequate medium in enjoying Sea World Indonesia deserve an attention from the company it self. This research is aimed to identify any kinds of attribute that satisfied the visitors, how big is the satisfaction level of the visitors and the priorities that must be conducted by the company. The research method used in this research is a case study with the visitors of Sea World of Indonesia as the set of the case and, the visitor's satisfaction level Sea World Indonesia as the object researched.   The validity test and reliabilities test is done to see the validity and the reliability of the questioner as a main instrument of a data intake. Data analyze method used is Descriptive Analysis, Cochran Q Test Analysis, Importance and Pelformance Analysis. Result of the research showed that there are fourteen attributes that is capable to give satisfaction to the visitors which is; the diversity of the sea aquarium attritiute, the diversity of the freshwater aquarium, the main aquarium, the dugong aquarium, the touch pool, the nameplate of each species, the incoming ticket price, the sanitation of the location, the freshness of the location, the security of the location, the security officer, the toilet, the parking area and the access to the location, The incoming ticket price attribute, the divefsity of the freshwater aquarium and the parking area gives a low satisfaction. The attribute of sea aquarium diversity, the main aquarium, the species nameplate, the freshness of the location, the toilet and the access to the location showed medium satisfaction level The dugong aquarium attribute, the touch pool, the sanitation of the location, the security of the location and the security officer have given high satisfaction for the visitors of Sea World Indonesia.